2022
DOI: 10.1161/circheartfailure.121.009028
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Venous Pressure-Assisted Exercise Stress Echocardiography in the Evaluation of Pulmonary Hypertension During Exercise in Patients With Suspected Heart Failure With Preserved Ejection Fraction

Abstract: Background: Identification of elevated pulmonary artery (PA) pressures during exercise may provide diagnostic, prognostic, and therapeutic implications in heart failure with preserved ejection fraction. Although widely performed, exercise stress echocardiography may underestimate true PA pressures due to the difficulty in estimating right atrial pressure (RAP) during exercise. We hypothesized that peripheral venous pressure (PVP) could allow for reliable estimation of RAP, and thus PA pressures dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…PASP was calculated as 4 × (the highest averaged TR velocity) 2 + estimated right atrial pressure (RAP). The RAP was estimated from the diameter of the inferior vena cava (IVC) and its respiratory change at rest and during exercise, coded as 3 mmHg (IVC diameter <2.1 cm with >50% respiratory collapse), 8 mmHg (borderline cases who did not meet criteria indicating either 3 or 15 mmHg), 15 mmHg (IVC diameter >2.1 cm with <50% respiratory collapse) 20 . The mPAP was calculated as 0.61 × PASP + 2 21 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PASP was calculated as 4 × (the highest averaged TR velocity) 2 + estimated right atrial pressure (RAP). The RAP was estimated from the diameter of the inferior vena cava (IVC) and its respiratory change at rest and during exercise, coded as 3 mmHg (IVC diameter <2.1 cm with >50% respiratory collapse), 8 mmHg (borderline cases who did not meet criteria indicating either 3 or 15 mmHg), 15 mmHg (IVC diameter >2.1 cm with <50% respiratory collapse) 20 . The mPAP was calculated as 0.61 × PASP + 2 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The RAP was estimated from the diameter of the inferior vena cava (IVC) and its respiratory change at rest and during exercise, coded as 3 mmHg (IVC diameter <2.1 cm with >50% respiratory collapse), 8 mmHg (borderline cases who did not meet criteria indicating either 3 or 15 mmHg), 15 mmHg (IVC diameter >2.1 cm with <50% respiratory collapse). 20 The mPAP was calculated as 0.61 × PASP + 2. 21 RV-PA coupling was assessed by TAPSE/PASP and TAPSE/PASP <0.36 was defined as abnormal RV-PA coupling.…”
Section: Baseline Echocardiographymentioning
confidence: 99%
“…Prior studies reported a close relationship between RAP and peripheral venous pressure at rest [ 56 , 57 ]. Our group recently demonstrated that the measurement of peripheral venous pressure may be a reliable alternative to RAP measurement during diastolic stress echocardiography [ 58 ].…”
Section: Exercise Echocardiography Methodsmentioning
confidence: 99%
“…The sensitivity of exercise echocardiography for EIPH is imperfect because the technique underestimates exercise PASP-not just because of the limitations of TR velocity but also because of the shortcomings of our noninvasive approach to measuring RA pressure. Although the pathway to the clinical adoption of PVP measurement is unclear, the study by Yang et al 13 serves as a reminder of the limits of agreement between hemodynamic exercise echocardiography and invasive measurements. Examining the PASP response to increased stroke volume may be the key to earlier diagnosis and intervention in a variety of diseases, including scleroderma 14 and heart failure with preserved ejection fraction.…”
Section: See Article By Yang Et Almentioning
confidence: 99%
“…In this issue of Circulation: Heart Failure , Yang et al 13 have hypothesized that peripheral venous pressure (PVP) could provide reliable estimation of right arterial pressure (RAP) with exercise, and thus more accurate pulmonary artery pressures during exercise stress echocardiography. They studied this in 2 steps.…”
mentioning
confidence: 99%